PENGARUH MEDIA DENGAN KRITERIA SALINITAS TANAH SALIN DAN NON SALIN TERHADAP EFEKTIVITAS DAN INFEKTIVITAS ISOLAT BAKTERI Rhizobium sp TOLERAN SALINITAS PADA TANAMAN KEDELAI (Glycine max L. Merril) - Clara Emanuela Prasetyani; Yulia Nuraini; Didik Sucahyono (Jurnal Tanah dan Sumberdaya Lahan, 2021)
Demand for the consumption of soybeans in 2014 was very high amounting to 10.91 kg capita-1 year-1 while soybean production was only 955 thousand tons. Soybean production can be increased by expanding the planting area including saline land areas. The use of soil microbes Rhizobium sp can help overcome this because Rhizobium sp can find symbiosis with soybean plants so that it allows the absorption of nitrogen nutrients for the growth of soybean plants. This study was aimed to determine and analyze the effect of saline soil on the effectiveness and infectivity of Rhizobium sp. inoculated to soybean plants on soil chemical and biological properties and plant growth. The study was conducted using a randomized block design consisting of 10 treatments and 3 replications. The results showed that the bacterial inoculation gave better plant growth than the control treatment on saline and non-saline soils. The high number of colonies was able to increase the number of effective root nodules and N-plant uptake and produced good plant growth with the best results. The inoculation treatment of isolate 12 on non-saline soil yielded N absorption value of 0.32 g plant-1, effective root nodules of 87.67 g plant-1, effective root nodule dry weight of 0.74 g plant-1, and plant height of 134.3 cm. Â On the biological properties of isolate 12 inoculation treatment on non-saline soil had the highest yield for the number of isolate colonies of 305.45 Ã— 105 CFU mL-1.